Quorum-sensing inhibitor potential of trans-anethole aganist Pseudomonas aeruginosa - TINAZ, GÜLGÜN (WILEY, 2018)
AimsQuorum sensing (QS) is a cell-cell communication system used by a broad spectrum of pathogenic bacteria to control the expression of their virulence genes. The interruption of QS systems of pathogenic bacteria has been considered as a novel way to fight bacterial diseases. In this study, trans-anethole, the main component of anise (Pimpinella anisum) oil was examined for its QS inhibitor (QSI) potential in an attempt to identify novel QSI compound effective against opportunistic pathogen Pseudomonas aeruginosa. Methods and ResultsThe preliminary screening of QSI capacity of trans-anethole was determined using a quorum-sensing inhibitor screen (QSIS) assay. The QSIS assay indicated that trans-anethole has QSI properties. QSI capacity of trans-anethole was further confirmed by lasB-gfp fussion assay and virulence factor assays. A sub-MIC of trans-anethole reduced the expression of lasB by 57%, elastase production by 59%, protease production by 56%, pyocyanin production by 95% and swarming motility by 68% without inhibiting growth of Pseudomonas aeruginosa PA01. Molecular docking and protein-ligand interaction studies were performed to understand the molecular mechanism underlying inhibitory activity of trans-anethole. The results of these analysis suggested that trans-anethole fits within the binding site of the LasR protein of P. aeruginosa. ConclusionTrans-anethole has the potential to inhibit QS-regulated virulence factors in P. aeruginosa by binding to LasR protein, similar to its natural ligand N-(3-oxododecanoyl)-l-homoserine lactone. Significance and Impact of the StudyIn this study, for the first time, it was demonstrated that trans-anethole has the potential to disrupt bacterial communication and can be developed as a novel QSI to combat with P. aeruginosa and other clinically significant pathogens.
Keywords: antibiotic resistance; P. aeruginosa; quorum-sensing inhibitors; trans-anethole; virulence factors; MOLECULAR DOCKING; BIOFILM FORMATION; PLANT; VIRULENCE; ANTIBIOTICS; ESTRAGOLE; BACTERIA; MOTILITY; EUGENOL; SYSTEM